The labor feat of the Soviet people during the Great Patriotic War (on the example of the construction of the Sursky defensive line and the Kazan bypass) - Mamaeva T. P., Litvinova A. M. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
this article examines the historical context of the construction of the Sursky defensive line and the Kazan bypass, their role in countering the offensive of strategic enemy forces. The author analyzes the process of border construction and the heroism of ordinary home front workers who worked on the construction of defensive structures.
Keywords: Великая Отечественная война; строительство; construction; население; population; Сурский оборонительный рубеж; Казанский обвод; The Great Patriotic War; Sursky defensive line; Kazan bypass